2019
DOI: 10.1021/acs.jnatprod.8b00732
|View full text |Cite
|
Sign up to set email alerts
|

Spiro[3.5]nonenyl Meroterpenoid Lactones, Cryptolaevilactones G–L, an Ionone Derivative, and Total Synthesis of Cryptolaevilactone M from Cryptocarya laevigata

Abstract: A CH3OH–CH2Cl2 (1:1) extract (N025439) of the leaves and twigs of Cryptocarya laevigata furnished eight new compounds, 1–8. Based on extensive 1D and 2D NMR spectroscopic data examination, the new δ-lactone derivatives 1–6 are monoterpene–polyketide hybrids containing a unique spiro[3.5]­nonenyl moiety. Their trivial names, cryptolaevilactones G–L, follow those of the related known meroterpenoids cryptolaevilactones A–F. Cryptolaevilactone L (6) contains 11,12-cis-oriented substituents, while the other cryptol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…On the other hand, 1 – 4 could be formed by a coupling of obolactone ( 9 ) or 7′,8′-dihydroobolactone ( 10 ) to (2 S /2 R )-5,7-dihydroxyflavanone (Scheme ). Therefore, a C-17 R configuration of 1 – 4 was assigned deductively by comparison of their NMR data with those of 9 and 10 , which was also consistent with most of the reported natural α-pyrones in the genus Cryptocarya displaying the same configurations to date. There have been only four complex flavanones , and one complex chalcone with similar bicyclic spiroketal skeletons reported before. However, the relative configurations of the three remaining asymmetric carbons at C-11, C-13, and C-15 of these known compounds were not discussed in detail, and their absolute configurations were left undetermined.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, 1 – 4 could be formed by a coupling of obolactone ( 9 ) or 7′,8′-dihydroobolactone ( 10 ) to (2 S /2 R )-5,7-dihydroxyflavanone (Scheme ). Therefore, a C-17 R configuration of 1 – 4 was assigned deductively by comparison of their NMR data with those of 9 and 10 , which was also consistent with most of the reported natural α-pyrones in the genus Cryptocarya displaying the same configurations to date. There have been only four complex flavanones , and one complex chalcone with similar bicyclic spiroketal skeletons reported before. However, the relative configurations of the three remaining asymmetric carbons at C-11, C-13, and C-15 of these known compounds were not discussed in detail, and their absolute configurations were left undetermined.…”
Section: Resultssupporting
confidence: 84%
“…250 species distributed widely in tropical and subtropical areas throughout the world . Many species of Cryptocarya have been investigated, which has led to the discovery of various natural products mainly including α-pyrones and alkaloids, together with complex flavonoids , and characteristic flavonoids in the genus Cryptocarya with a hydrogenated A-ring containing a C-5 acetic acid/lactone group. , A wide range of biological activities including antitrypanosomal, antimalarial, cholinesterase inhibitory, antituberculosis, antimicrobial, anti-inflammatory, and especially cytotoxic ,,, activities have been revealed for many of these compounds.…”
mentioning
confidence: 99%
“…The genus Cryptocarya , family Lauraceae, consists of 200–250 species mainly distributed in the tropical and subtropical areas except Central Africa [1] . Previous phytochemical investigations on some Cryptocarya species have reported a number of α‐pyrones, [2–11] alkaloids [12–15] along with two types of unique flavonoids as complex flavonoids [2,16–20] and cryptocaryanone‐type flavonoids with a dearomative A‐ring containing an acetic acid/lactone unit at C‐5 [3–6,17–23] . Many of these isolates have been revealed with strong cytotoxicity [5,12,15,19–21] together with the other pharmaceutical effects such as anti‐inflammatory, [23] antimalarial, [8] antimicrobial, [20] antitrypanosomal, [4] antituberculosis [18] and cholinesterase inhibitory [13] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve meroterpenoid lactones [cryptolaevilactones (CLs) A-L (1-12)] were first isolated from a 50% MeOH/CH 2 Cl 2 extract (N025439) of the leaves and twigs of Cryptocarya laevigata by our group 1,2) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The absolute configurations at C-8 of CLs A-C (1-3) were determined by using a modified Mosher method. 1) Subsequently, nuclear Overhauser effect spectroscopy (NOESY) correlations between H-6 and H-8 of the related Michael adducts, CLs D-F (5-7), revealed that these hydrogen atoms have a syn relationship. The relative configurations of the four asymmetric carbons on the spiro ring were also assigned from NOESY correlations and ECD calculations.…”
Section: Introductionmentioning
confidence: 99%